Prognostication and Precognition as Novums in Postwar SF - Smith, Alexander Kingsbury (Science-Fiction Studies, 2021)
Very broadly speaking, beginning with the development of a social science-fictional mode, a number of postwar authors began exploring how forms of exceptionally accurate foresight might effect the development of a society. The social effects of the mobilization of extraordinary forms of prognostication were explored by numerous authors in the 1940s and 1950s, including Alfred Bester, Philip K. Dick, A.E. vanV ogt, and Isaac Asimov. This became a significant, but theoretically and critically understudied, motif in sf during the 1960s and 1970s. Relative to the study of prognostication in history, this body of sf literature provides a unique perspective on the relationship between predictive methods and governance, offering a corpus of theoretical reflections on how the implementation of hypothetical, infallible (or nearly infallible) prognostic systems could affect different types of social order. In this essay, I will briefly explore the development of prognostication and precognition as socially embedded novums and investigate what these sources tell us about prognostication in history when viewed through the lens of Western metaphysics and the Western literary imagination. In doing so, I propose a binary taxonomy as a heuristic, organizing texts with prognostication or precognition as their central novum into two general modes: (1) positivist/techno-optimist and (2) romantic/techno-pessimist. The intellectual history of these tendencies in the literature is explored and compared through several exemplary texts.
CRIS-Team WoS Importer:2021-07-09